The Analysis of Politeness Strategies and Kinship Relationship: A Study Case of Wawonii Educational Background Compared to American - Rizki Ashariah Sarwin; Abdul Hakim Yassi; Sukmawaty Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This research aims (1) to analyze the types of politeness strategies used by Wawonii speakers compared to American in daily conversations, and (2) to explore the educational background defined politeness strategies of Wawoniiese compared to American. The research used the quantitative research method.  Wawoniiese data were collected from 32 respondents in North East Wawonii through questionnaire, observation, interview, and recorded dialogue form of speech. American data were taken from transcribed conversations of selected movies. The research result found that Wawoniiese and American speakers used four of the Politeness Strategies by Brown and Levinson. They were Bald-on-record, Positive Politeness, Negative Politeness, and Off-record. Furthermore, this research also found that the politeness systems of young and older people are almost similar, for instance, both systems showed 93,75% of speakers used deferent speech variety when talking to Parents-in-law. Meanwhile, when adding the educational background, the result showed more variations in politeness systems. Despite having age differences the older and younger family members can have conversations in mixed and casual varieties due to the influence of the educational background of speakers. For instance, the politeness systems by well-educated showed 37,5% of speakers used mixed speech variety and 56,25% of speakers used casual speech variety when talking to older cousins. Therefore, in Wawonii notably in North East Wawonii the educational background of speakers is the factor that significantly defines the choice of people's utterances compared to the variable of age. Hence, this research concluded that educational background influenced the politeness strategies of Wawonii speakers but not of American.